The Process of Identity formation of Local Products in the Northeast Central - Potiwan , Piyaluk; Rittisut, Prapatsorn; Uoongoen, Nutcha (Journal for Developing the Social and Community, 2024)
This research paper is part of a research project of innovations to raise community product standards and cultural tourism to Reduce Economic and Social inequality leading to the development of creative wisdom based on the King’s Philosophy in central northeastern area, which has an objective of this research is to study the nature of product style creation through the search for distinctive identities to design brands. The study was conducted in the north-central provinces, consisting of Roi Et Province, Khon Kaen Province, Maha Sarakham Province, and Kalasin Province, by selecting research areas and units for analysis at the community level, which are communities where goods are produced and collected, in which a group of people provide insight into the production of community products from production to distribution as well as play a role in conservation. The key informants were a group of community leaders, manufacturers, and distributors; marketing and product design totaled 40 people. Data was collected through interviews, and qualitative data were analyzed with content analysis. The results of the research showed that the finding and synthesizing of local and community identities can be applied to the design of the emblem to develop product styles. This includes increasing channels for marketing and distribution as well as developing marketing strategies that are appropriate to that type of product. Creating an identity for community products is an important factor in the success of raising the standard of community products for economic development. However, the development of community products to create standards should be defined and supported in accordance with the lifestyle of the community. Due to different conditions and restrictions, it is not possible to use the same standards or the same identity to raise the level of development.